Some pair-wise classifications employed in historiography - Christopher Torr (South African Journal of Economic and Management Sciences, 2001)
Various pair-wise classifications have been employed in historiography, the most recent being Waterman's distinction between intellectual history and the history of economic analysis. Other dichotomies are rational reconstruction and historical reconstruction, the context of discovery and the context of justification, internal history and external history and relativist and absolutist accounts. In the 1930s Butterfield differentiated the Whig interpretation of history from the non-Whig approach. Another dichotomy which has a much older history is the distinction between text and context. Perhaps the oldest dichotomy of all is the distinction between particulars and universals. An attempt is made to show the age-old controversy between nominalism and universals provides a common thread to the dichotomies discussed in this paper.